2012
DOI: 10.1016/j.cell.2012.09.011
|View full text |Cite
|
Sign up to set email alerts
|

SMN Is Required for Sensory-Motor Circuit Function in Drosophila

Abstract: Summary Spinal muscular atrophy (SMA) is a lethal human disease characterized by motor neuron dysfunction and muscle deterioration due to depletion of the ubiquitous Survival Motor Neuron (SMN) protein. Drosophila SMN mutants have reduced muscle size and defective locomotion, motor rhythm and motor neuron neurotransmission. Unexpectedly, restoration of SMN in either muscles or motor neurons did not alter these phenotypes. Instead, SMN must be expressed in proprioceptive neurons and interneurons in the motor ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
170
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 176 publications
(187 citation statements)
references
References 71 publications
17
170
0
Order By: Relevance
“…Notably, similar early failure to produce firing activity was reported for MNs in mouse and Drosophila models of spinal muscular atrophy (SMA), a rapidly progressing early onset motoneuron disease (Mentis et al, 2011). In the SMA model failures in MN excitation involved defects in proprioceptive Ia synaptic excitation of MNs, and MN degeneration could be rescued by either direct activation of MNs or by correcting the mutation in primary afferent proprioceptive neurons (Figure 2) Imlach et al, 2012). These findings of how MNs are affected in SMA are reminiscent of non-cell-autonomous mechanisms of disease in HD, where loss of cortical input activity leads to inactivation and degeneration of vulnerable medium spiny neurons (see below).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 53%
“…Notably, similar early failure to produce firing activity was reported for MNs in mouse and Drosophila models of spinal muscular atrophy (SMA), a rapidly progressing early onset motoneuron disease (Mentis et al, 2011). In the SMA model failures in MN excitation involved defects in proprioceptive Ia synaptic excitation of MNs, and MN degeneration could be rescued by either direct activation of MNs or by correcting the mutation in primary afferent proprioceptive neurons (Figure 2) Imlach et al, 2012). These findings of how MNs are affected in SMA are reminiscent of non-cell-autonomous mechanisms of disease in HD, where loss of cortical input activity leads to inactivation and degeneration of vulnerable medium spiny neurons (see below).…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 53%
“…Although SMA is one of the most studied genetic disorders, the mechanism that leads to motoneuron loss is poorly understood. Because SMN is involved in the biogenesis of spliceosomal snRNPs, many studies of molecular aspects of SMA are focused on deciphering the impact of SMN loss on snRNP biogenesis and activities (Chari et al, 2009;Gabanella et al, 2007;Imlach et al, 2012;Lotti et al, 2012;Pellizzoni, 2007;Winkler et al, 2005;Workman et al, 2009;Zhang et al, 2008). SMN makes a crucial contribution to the activity of the splicing machinery by interacting with spliceosome-associated proteins, whereas methylation of H3K79 is positively correlated with the transcription process.…”
Section: Discussionmentioning
confidence: 99%
“…This complex is implicated in the nucleocytoplasmic transport of small nuclear RNAs (snRNAs) and in their maturation to small nuclear ribonucleoproteins (snRNPs) as part of the spliceosomal complex (Akten et al, 2011;Deryusheva et al, 2012;Fischer et al, 1997;Leung et al, 2011;Liu et al, 1997;Makarov et al, 2012;Massenet et al, 2002;Matera and Shpargel, 2006;Sebbag-Sznajder et al, 2012). Studies using different models of SMA have suggested that the severity of the disease could correlate with the inefficiency of snRNP maturation, and as a consequence, to defective splicing of target pre-mRNAs (Chari et al, 2009;Gabanella et al, 2007;Imlach et al, 2012;Lotti et al, 2012;Pellizzoni, 2007;Winkler et al, 2005;Workman et al, 2009;Zhang et al, 2008). The implication of SMN in such a fundamental molecular pathway in cells of all origins is difficult to reconcile with the selective involvement of the neuromuscular system in SMA.…”
Section: Introductionmentioning
confidence: 99%
“…This autosomal recessive neuromuscular disorder is most commonly caused by homozygous deletion of the survival motor neuron 1 (SMN1) gene, leading to reduced levels of ubiquitously expressed full-length SMN protein (1,3). SMA is primarily characterized by degeneration of lower motor neurons and atrophy of skeletal muscle (3,4), with functional and structural disruption of synaptic connectivity at neuromuscular junctions (NMJ) and in the spinal cord occurring during the early stages of disease pathogenesis (5)(6)(7)(8)(9). However, recent studies have revealed that SMA, particularly in its most severe forms, is a multisystem disorder (10), with other regions of the nervous system also being affected (e.g., the hippocampus; ref.…”
Section: Introductionmentioning
confidence: 99%